2010
DOI: 10.1007/978-3-642-16170-4_24
|View full text |Cite
|
Sign up to set email alerts
|

The Price of Anarchy in Network Creation Games Is (Mostly) Constant

Abstract: We study the price of anarchy and the structure of equilibria in network creation games. A network creation game is played by n players {1, 2, . . . , n}, each identified with a vertex of a graph (network), where the strategy of player i, i = 1, . . . , n, is to build some edges adjacent to i. The cost of building an edge is α > 0, a fixed parameter of the game. The goal of every player is to minimize its creation cost plus its usage cost. The creation cost of player i is α times the number of built edges. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
59
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(64 citation statements)
references
References 11 publications
5
59
0
Order By: Relevance
“…The max-distance network creation game, introduced and studied by Demaine et al [2], is a key variant of the original game, where the usage cost takes into account the maximum distance instead. The main result of this paper shows that for α ≥ 23 all equilibrium graphs in the max-distance network creation game must be trees, while the best bound in previous work is α > 129 [3]. We also improve the constant upper bound on the price of anarchy to 3 for tree equilibria.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…The max-distance network creation game, introduced and studied by Demaine et al [2], is a key variant of the original game, where the usage cost takes into account the maximum distance instead. The main result of this paper shows that for α ≥ 23 all equilibrium graphs in the max-distance network creation game must be trees, while the best bound in previous work is α > 129 [3]. We also improve the constant upper bound on the price of anarchy to 3 for tree equilibria.…”
mentioning
confidence: 84%
“…It has been proved that if all equilibrium graphs are trees, the price of anarchy will be constant in either sum-distance setting or max-distance setting [1,3,9]. This result will help to justify the famous small-world phenomenon [10,11], which suggests selfishly built networks are indeed very efficient, at least not unacceptably bad.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the authors show that the price of anarchy is constant for α ≤ √ n and for α ≥ 12n log n. In the latter case they prove that any pure equilibrium is a tree. This bound was improved in [35], where it was shown that for α ≥ 273n all pure equilibria are trees. Later on, in [32], this was further improved by showing that it even holds for α ≥ 65n.…”
Section: Related Literaturementioning
confidence: 99%
“…The paper [16] introduces a version of the game where the distance cost of a player is defined the maximum distance from i to any other player (instead of the sum of distances), and studies the price of anarchy for these games. Further results on those games can be found in [35]. Another natural variant of a cost sharing game is one where both endpoints of an edge can contribute to its creation, as proposed in [34], or must share its creation cost equally as proposed in [15] and further investigated in [16].…”
Section: Related Literaturementioning
confidence: 99%
“…Upper bounds were shown for ULF and tight bounds for BLF. For ULF, improved bounds were recently shown in [MS10].…”
Section: Related Workmentioning
confidence: 99%